Studi Penerapan Inovasi Teknologi Informasi dengan Metode Technology Watch and Competitive Intelligent (Tw-Ci) - Febriana, Trisna (Bina Nusantara University, 2014)
The development of information technology creates a new way of many aspects in life. Innovations in this technology affect toward business environment, especially banking, which makes the business run dynamically. All of the transaction of a bank will be processed easily with the presence of computer. A bank needs all of the changes in order to compete with competitors, and that includes changes in information technology. The more expanding and complex facilities applied in a bank, the more complex and diverse technology adopted by a bank. The implementation of technology information in banking is not simple, it needs a long term planning and maintenance system so that all of the technology information facilities could run well and give a significant impact. Technology monitoring or benchmarking is one of the options that is taken by a bank to maintain its existence in facing the tight competition. To create technology innovation in banking need a monitoring technology method that is named TW-CI. This method is used to fulfill business needs in facing a competition to get and choose information that can be used to support a decision, so that the innovation applied by a bank is efficient and finally give an added value and also create entanglement between a bank and its consumer.